Burden and Gender inequalities around Informal Care - Cascella Carbó, Giuliana F.; García-Orellán, Rosa (Investigación y Educación en Enfermería, 2020)
This work comes from the interest and need to understand the problems arising from the activity of caring for dependent people, in the world and particularly in the European region. Altogether, it seeks to understand the consequences of informal care on the caregiver adding to the debate a gender perspective. Through a multidisciplinary bibliographic review, the current care crisis becomes clear. The demographic and socio-cultural changes in recent years are causing dependency to increase dramatically, while putting at risk the availability of informal caregivers. Several studies have shown that women are the ones on whom the burden of care mainly falls. Therefore, under the gender perspective, it becomes clear that the consequences of caregiver burden increase gender inequalities worldwide. The study analyzes the current situation and underlines the need to promote alternatives and opportunities so that care is shared and does not fall only on the female gender. Solutions need to be included in public and community health interventions and policies, and to this respect, nurses play an important role in changing the care paradigm. How to cite this article: Cascella GF, García-Orellán R. Burden and Gender inequalities around Informal Care . Invest. Educ. Enferm. 2020; 38(1):e05.